Sepsis protocol adherence and emergency department overcrowding: An observational study - Arifani, Nisa; Mulyati, Leli; Sasmito, Priyo; Sujana, Treesia; Gayatri, Sri Wahyuni; Astuti, Novia Dwi; Librianty, Nurfanida; Lie, Sukirman; Deviana, Elina; Ihsan , Farly (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Emergency Department (ED) overcrowding is a persistent global challenge that affects the quality and timeliness of patient care, particularly for sepsis management. Despite established guidelines such as the hour-1 sepsis bundle and national sepsis guideline, adherence remains inconsistent. Purpose: To analyze the relationship between sepsis protocol compliance and emergency unit crowding. Method: A retrospective observational cohort study was conducted, analyzing adult sepsis and septic shock patients triaged as Priority 1. Data on patient demographics, sepsis severity scores, ED occupancy rates, and adherence to sepsis protocols using the Hour-1 sepsis bundle and the National Sepsis Guideline were collected. Statistical analysis was performed using Fisher’s Exact Test to examine associations between ED overcrowding and compliance with sepsis protocols, with a significance threshold of p<0.05. Results: This study included 38 cases with a mean age of 56.6 years and the majority (52.6%) of patients were female. Most cases were diagnosed with septic shock (55.3%) and the average occupancy rate of the emergency department was 80.8%. Serum lactate measurements were performed in 68.4% of cases, blood culture sampling in 21.1%, and broad-spectrum antibiotics were given in 94.7%. Full compliance with both sepsis protocols was only 5.3%. Compliance with fluid resuscitation was high at 97.4%, while compliance with blood culture sampling was low at 5.3% and 7.9%. No significant association was found between protocol compliance and ED crowding (p > 0.05). Conclusion: There was no significant correlation between ED crowding and adherence to sepsis protocols. Strategic and clinical policy interventions are needed to improve adherence to sepsis management guidelines. Suggestion: Future research should investigate additional barriers to sepsis care, such as financial constraints, physician decision-making processes, and variations in adherence across healthcare settings to develop more comprehensive strategies to improve sepsis outcomes worldwide.